Restaurante de comidas tipicas Quimiag. - Barreno, Nataly (2010)
This document represents a research work carried out in the Químiag parish, which presents a series of difficulties related to the existence of restaurants fulfilling the categorization requirements and characteristics, which allow the offer of a service with excellence in quality and products, this is the reason why we need to know the feasibility for the creation of a Typical Food Restaurant acquiring a revealed prestige, at the same time to support in the development of the parish by increasing the working sources and providing the population and people who visit the parish a cozy place to go to satisfy the feeding service quality needs.